Combination of Implicit Integration and Collision Response for Cloth Simulation (Journal of Fiber Bioengineering and Informatics, 2012)
This paper implements efficient techniques for cloth simulation in the area of cloth model, numericalintegration, collision detection and response. The whole procedure combines the accurate bending modelwith implicit integration and collision response. Collision response remains a serious difficulty in clothsimulation, especially with implicit integration. We propose a general scheme that integrates collisionresponse into implicit models recovering most of the nice draping movements of the cloth. Collisiondetection between human body and cloth is accelerated by Axis Aligned Bounding Box (AABB). Acloth draped on a human model is tested for the combined techniques we put forward. Experimentalresults reveal that this procedure is suitable for the accurate cloth simulation which preserves folds andwrinkles. The scheme that combines implicit integration and two-stage collision response is efficient forcloth simulation.